(untitled) (Ágora Journal, 2022)
This article aims to discuss the passage of the yellow fever epidemic in Recife in the mid-nineteenth century. Starting from the understanding of the disease as a social phenomenon that is projected beyond biological factors, we sought to observe the succession of events that marked the passage of yellow fever through the capital of the Pernambuco province, based on the responses of Recife society and the actions of the government to the development of the epidemic phenomenon. In order to observe this dynamic, an analysis was carried out of the Reports of the Presidency of the Province of Pernambuco, the Collection of Works of the General Council of Public Health and the periodicals entitled Diário de Pernambuco and A Imprensa.